Breastfeeding: Maternally Transferred Allergens in Breast Milk: Protective or Sensitizing?. Issue 15 (22nd June 2022) - Schocker, Frauke; Jappe, Uta
Abstract: According to a thorough literature search, the following allergen sources have been associated with allergy symptoms in the exclusively breastfed child: hen's egg, cow's milk, peanut, trout. Subsequently, several studies use the advantage of molecular allergology and investigate the potential transfer of single allergens into breastmilk. This is shown for caseins, whey proteins, gliadin, ovalbumin, ovomucoid, the peanut allergens Ara h 2 and Ara h 6, as well as the inhalant allergens Der p 1 and Blo t 5. It is still a matter of debate whether or not food allergens transferred via breastfeeding to the baby promote allergic sensitization or induce tolerance and via which mechanisms they may shift the immune response to the one or other side. Noteworthy, some breastfed children are described to be sensitized to foods before being exposed to solid foods, and this exposure may have occurred through breastmilk. In the light of these findings the investigation of food allergens transferred from the mother's diet into breastmilk and their impact on sensitization or allergy prevention remains a current topic in research. This review describes breastmilk in its composition and provides data on the identification of food allergens therein including human and mouse studies. Abstract : Food allergens transferred from the mother's diet into breastmilk may be crucial as the first food allergen exposure for the breastfed infant to be either sensitized or to develop oral tolerance. The identification of allergens in breastmilk and an understanding of allergen exposure are prerequisites for the investigation of sensitizing or protective properties.